2007
DOI: 10.1586/14737175.7.11s.s27
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clinician and patient attitudes on clinical decision making for the symptomatic menopausal woman with or without comorbidity

Abstract: Culture, individual health beliefs and distressing symptoms frequently determine women's perceptions of their menopausal transitions. Women's perceptions of mental health problems and the acceptability of different interventions greatly affect if and what a woman is willing to try as a treatment option and whether or not she will accept the possibility that her menopausal symptoms represent a comorbidity with a diagnosis, such as depression or anxiety. These perceptions have a significant impact on women's cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…The women with more than four symptoms were more likely to visit hospitals, compared to those women suffering from three or less symptoms. This result was similar to a review, in which women would not seek treatment unless they experienced multiple or severe symptoms [32]. It was also consistent with one of our other hospital-based studies, which showed women without symptoms or with only two or fewer menopausal symptoms were less likely to visit hospitals promptly compared to those experiencing five or more symptoms [33].…”
Section: Discussionsupporting
confidence: 89%
“…The women with more than four symptoms were more likely to visit hospitals, compared to those women suffering from three or less symptoms. This result was similar to a review, in which women would not seek treatment unless they experienced multiple or severe symptoms [32]. It was also consistent with one of our other hospital-based studies, which showed women without symptoms or with only two or fewer menopausal symptoms were less likely to visit hospitals promptly compared to those experiencing five or more symptoms [33].…”
Section: Discussionsupporting
confidence: 89%
“…Women who lack knowledge of menopause are more likely to have negative attitudes towards it. Research suggests that the severity of menopausal symptoms affects women’s attitudes towards menopause, with fewer symptoms being associated with more positive attitudes towards menopause [ 36 ]. A survey of perimenopausal women conducted in the UK showed that more than 60% of women had no understanding of menopause at all [ 37 ], whereas Italian studies indicated that more than half of women had never received menopause-related health education [ 38 ].…”
Section: Discussionmentioning
confidence: 99%